PRL1 Promotes Glioblastoma Invasion and Tumorigenesis via Activating USP36-Mediated Snail2 Deubiquitination - Qiu, Wenjin; Cai, Xiaomin; Xu, Kaya; Song, Shibin; Xiao, Zumu; Hou, Yunan; Qi, Xiaolan; Liu, Feng; Chen, Yimin; Yang, Hua; Chu, Liangzhao; Liu, Jian (Frontiers in Oncology, 2022)
Regenerating liver phosphatase 1 (PRL1) is an established oncogene in various cancers, although its biological function and the underlying mechanisms in glioblastoma multiforme (GBM) remain unclear. Here, we showed that PRL1 was significantly upregulated in glioma tissues and cell lines, and positively correlated with the tumor grade. Consistently, ectopic expression of PRL1 in glioma cell lines significantly enhanced their tumorigenicity and invasion both in vitro and in vivo by promoting epithelial-mesenchymal transition (EMT). Conversely, knocking down PRL1 blocked EMT in GBM cells, and inhibited their invasion, migration and tumorigenic growth. Additionally, PRL1 also stabilized Snail2 through its deubiquitination by activating USP36, thus revealing Snail2 as a crucial mediator of the oncogenic effects of PRL1 in GBM pathogenesis. Finally, PRL1 protein levels were positively correlated with that of Snail2 and predicted poor outcome of GBMs. Collectively, our data support that PRL1 promotes GBM progression by activating USP36-mediated Snail2 deubiquitination. This novel PRL1/USP36/Snail2 axis may be a promising therapeutic target for glioblastoma.